IZDPWM-Based Feedforward Controller for Grid-Connected Inverters Under Unbalanced and Distorted Conditions - Shayestehfard, A.; Mekhilef, Saad; Mokhlis, Hazlie (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In grid-connected inverters, a feedforward controller accurately compensates for a large number of the harmonic components of the injected current. This controller is fast and directly tackles the grid dynamic voltage disturbances without doing any further harmonic analysis. A feedforward controller was introduced to a three-phase grid connection with a wye configuration; however, for the widespread delta connections, such a scheme is less established. Moreover, the nonsinusoidal profile of the grid voltage waveform makes the online conversion of line-to-line values into phase values impossible. In this paper, implicit zero-sequence discontinuous pulse width modulation (IZDPWM) based feedforward control is implemented on the two-level grid-connected inverter. Regardless of the grid topology, the IZDPWM-based controller ensures sinusoidal current injection to the grid under balanced, unbalanced, and distorted conditions.